Duchenne muscular dystophy: A short review and treatment update - Topaloglu, Haluk (Iranian Journal of Child Neurology, 2021)
After advances in clinical care and newer efforts in therapeutic approaches, life span has lengthened in Duchenne muscular dystrophy (DMD). Starting from eary 1980s, each decade lead to a five year gain. DMD is not simply a monogenic X-linked disorder, it is a multisystemic condition. Pulmonary, cardiac, endocrine, gastrointestinal, and bone health aspects need careful monitoring along with pyschology, physiotherapy, social and family as a whole. Molecular treatments are becoming facts, which some are already at hand. Some others are expected to be available within the next two years.